Use of cangrelor in patients with acute coronary syndromes undergoing percutaneous coronary intervention: Study design and interim analysis of the ARCANGELO study. Issue 9 (22nd June 2022) - De Luca, Leonardo; Calabrò, Paolo; Chirillo, Fabio; Rolfo, Cristina; Menozzi, Alberto; Capranzano, Piera; Menichelli, Maurizio; Nicolini, Elisa; Mauro, Ciro; Trani, Carlo; Versaci, Francesco; Tomai, Fabrizio; et al.
Abstract: Background: The itAlian pRospective Study on CANGrELOr (ARCANGELO) was aimed to assess the safety of using cangrelor during percutaneous coronary intervention (PCI) in patients with acute coronary syndromes (ACS) in the daily practice. Hypothesis: The safety of cangrelor after the transition to oral P2Y12 inhibitors was evaluated as the incidence of bleeding outcomes in the 30 days following PCI according to postauthorization safety study guidelines. Methods: Adults with ACS who were treated with cangrelor in one of the 28 centers involved in the study. Patients who consented to participate were followed in the 30 days following their PCI. Bleedings (Bleeding Academic Research Consortium [BARC] classification), major adverse cardiac events (MACEs), and adverse events were recorded. The interim results at two‐thirds of the enrollment period are presented. Results: A total of 17 bleedings were observed in the 320 patients who completed the study at this stage. All bleedings were classified as BARC Type 1–2, except for one case of Type 3a (vessel puncture site hematoma). Four patients experienced MACEs (2 acute myocardial infarctions, 1 sudden cardiac death, 1 noncardiovascular death due to respiratory distress, and multiorgan failure). None of the bleedings was rated as related to cangrelor. Conclusions: The interim results of the ARCANGELO study provide a preliminary confirmation that the use of cangrelor on patients with ACS undergoing PCI is not associated with severe bleedings.